Suppression of IL‐12/IL‐23 p40 subunit in the skin and blood of psoriasis patients by Tofacitinib is dependent on active interferon‐γ signaling in dendritic cells: Implications for the treatment of psoriasis and interferon‐driven diseases. Issue 6 (21st March 2022) - Vincken, Nanette L. A.; Welsing, Paco M. J.; Silva‐Cardoso, Sandra C.; Bekker, Cornelis P. J.; Lopes, Ana P.; Olde Nordkamp, Michel; Leijten, Emmerik F. A.; Radstake, Timothy R. D. J.; Angiolilli, Chiara
Abstract: Interleukin (IL)‐12 and IL‐23 are pro‐inflammatory cytokines produced by dendritic cells (DCs) and associated with Psoriasis (Pso) and Psoriatic Arthritis (PsA) pathogenesis. Tofacitinib, a Janus kinase inhibitor, effectively suppresses inflammatory cascades downstream the IL‐12/IL‐23 axis in Pso and PsA patients. Here, we investigated whether Tofacitinib directly regulates IL‐12/IL‐23 production in DCs, and how this regulation reflects responses to Tofacitinib in Pso patients. We treated monocyte‐derived dendritic cells and myeloid dendritic cells with Tofacitinib and stimulated cells with either lipopolysaccharide (LPS) or a combination of LPS and IFN‐γ. We assessed gene expression by qPCR, obtained skin microarray and blood Olink data and clinical parameters of Pso patients treated with Tofacitinib from public data sets. Our results indicate that in DCs co‐stimulated with LPS and IFN‐γ, but not with LPS alone, Tofacitinib leads to the decreased expression of IL‐23/IL‐12 shared subunit IL12B (p40). In Tofacitinib‐treated Pso patients, IL‐12 expression and psoriasis area and severity index (PASI) are significantly reduced in patients with higher IFN‐γ at baseline. These findings demonstrate for the first time that Tofacitinib suppresses IL‐23/IL‐12 shared subunit IL12B in DCs upon active IFN‐γ signaling, and that Pso patients with higher IFN‐γ baseline levels display improved clinical response after Tofacitinib treatment.